2016
DOI: 10.1016/j.physe.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Chiral vectors-tunable electronic property of MoS2 nanotubes

Abstract: It has been demonstrated that the mechanical and electronic properties of materials change significantly when the external dimension are confined to the nanoscale. Consequently, one-dimensional (1D) transition-metal dichalcogenide (TMDC) nanotubes (NTs), obtained from scrolling two-dimensional (2D) TMDC, have attracted much attentions because of their intriguing properties wherein the chirality of NTs plays a key role in affecting the electronic properties. Taking into the amount of speculations on the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Moreover, theoretical studies have suggested that the band structure of WS 2 nanotubes changes depending on their diameter (less than ∼17 nm) due to a curvature effect and low dimensionality. 9) Therefore, WS 2 nanotubes with small diameters are advantageous for their tunable band gap, 9) carrier mobility, 12,13) and thermoelectric properties. 11) Thus, it is important to develop a technique to prepare WS 2 nanotubes with small diameters for device applications.…”
mentioning
confidence: 99%
“…Moreover, theoretical studies have suggested that the band structure of WS 2 nanotubes changes depending on their diameter (less than ∼17 nm) due to a curvature effect and low dimensionality. 9) Therefore, WS 2 nanotubes with small diameters are advantageous for their tunable band gap, 9) carrier mobility, 12,13) and thermoelectric properties. 11) Thus, it is important to develop a technique to prepare WS 2 nanotubes with small diameters for device applications.…”
mentioning
confidence: 99%
“…Thin nanotubes with a small diameter and few walls have great advantages for applications. , For instance, nanotubes with a small diameter can improve mechanical properties because they can endure a larger breaking strain . Additionally, theoretical studies suggested that small diameter nanotubes have a one-dimensional band structure due to quantum confinement, and we can tune the bandgap and enhance carrier mobility . However, the one-dimensional nature of TMDC nanotubes has not been revealed yet because of difficulties in the synthesis of thin nanotubes with a uniform diameter and wall number. It is important to develop a technique to prepare nanotubes with thin diameters in a relatively small distribution.…”
mentioning
confidence: 99%
“…Not surprisingly, chirality also influences the properties of MoS 2 nanotubes, such as electronic property which could be tuned by chiral vectors [71]. Mechanical and electronic properties of monolayer MoS 2 are also affected by the chiral vectors [72,73].…”
Section: Chirality Control In Nanostructured Mos 2 /Which Relates To ...mentioning
confidence: 99%